Exploring the role of sustainable logistics service providers in multinational supply chain cooperation: An integrated theory-based perspective - Su, Miao; Fang, Mingjie; Pang, Qiwei; Park, Keun-sik (Frontiers in Environmental Science, 2022)
In recent years, suppliers’ sustainability has been the primary source of conflict in multinational supply chains. How suppliers from developing nations may accomplish sustainable development and competitive advantage goals has become a tough issue inside the multinational supply chain, particularly in the agri-food cold chain. Using an integrated theory-based perspective, this paper analyzes how sustainable logistics service providers’ supply chain cooperation (MSCC) might drive the sustainable transformation of suppliers in developing nations. Between 1 June 2020 and 15 January 2021, we gathered feedback from 215 Chinese vendors and analyzed and discussed possible models using structural equation modeling. This study demonstrates that the sustainable practices of logistics service providers are the foundation for influencing the collaboration of suppliers in developing nations with regard to sustainability. In addition, the five-stage transnational supply chain cooperation based on the theory of innovation diffusion is an efficient strategy for ensuring the sustainable development of suppliers in developing nations. This paper examines the theoretical framework at the forefront of multinational supply chain sustainability development. This presents the most recent experience and policy application for suppliers from emerging nations to acquire a competitive advantage.